One-Component Thioxanthone Acetic Acid Derivative Photoinitiator for Free Radical Polymerization - Esen, Duygu S.; Temel, Gokhan; Balta, Demet K.; Allonas, Xavier; Arsu, Nergis (WILEY-BLACKWELL, 2014)
Acetic acid-based thioxanthone (TXCH2COOH) was synthesized and characterized and used as a photoinitiator for free radical photopolymerization of methyl methacrylate (MMA) in the absence and presence of a tertiary amine (MDEA) in different solvents. Different absorption properties were observed depending on the solvent. Fluorescence and phosphorescence experiments were also carried out successfully. The fluorescence quantum yield was found to be 0.09 and the phosphorescence lifetime was calculated as 138ms at 77K. The photoinitiator undergoes efficient intersystem crossing into the triplet state and the lowest triplet state possesses pi-pi* configuration. Laser flash photolysis experiments show that transient absorption of TXCH2COOH is similar to the parent thioxanthone and the triplet lifetime was calculated as 2.3 mu s at 630nm.
Keywords: COINITIATOR; ANTHRACENE; SYSTEMS; Biochemistry & Molecular Biology; Biophysics